Export production in a continental shelf with multisource nutrient supply - Zhang, Jing; Zhu, Lei; Guo, Xinyu; Wang, Yucheng; Feng, Jianlong; Zhao, Liang (Frontiers in Marine Science, 2024)
Export production, which is defined as the export of organic matter fixed by photosynthesis, is crucial for sustaining oceanic carbon uptake. The export route in the open ocean is the sinking of biogenic particles through the bottom of the euphotic layer. In contrast, the export routes in the shelf seas are the sinking of biogenic particles to the sediment and the horizontal transport of biogenic particles across the boundary of the shelf seas to the open ocean. The biogenic particles in the shelf seas are supported by multisource nutrients including riverine and oceanic ones. Their exports depend on the hydrodynamic conditions and biogeochemical processes responsible for different sources of nutrients. Here, a unique physical-biological coupled model with a tracking approach is applied to evaluate the export production supported by multisource dissolved inorganic nitrogen (DIN) over the East China Sea. The total export production is 6.83 kmol N s-1 (=17.16 Tg C yr-1), which is slightly lower than the reported atmospheric CO2 absorption. Approximately 80% of particulate organic nitrogen (PON) is exported via off-shelf transport, and the remaining 20% is buried in the sediment. The PON supported by DIN from rivers accounts for 8% of export production, with an e-ratio (export production/primary production) of 0.09. In comparison, that from the Kuroshio accounts for 64%, with an e-ratio of 0.22. This suggests that offshore areas here are more efficient in exporting local production than nearshore ones, largely supported by oceanic nutrients.